Analysis of the clinical application of ceftazidime-avibactam in China - Qing Wang; Ping Xu; Yangang Zhou (Elsevier, 2022)
Background: The efficacy and safety of ceftazidime-avibactam were mainly reported in phase II and phase III clinical trials, rarely in the real-world study. The limited real-world study which evaluated the clinical response of this drug shown inconsistent results. This study aimed to investigate the rationality of the clinical use of ceftazidime-avibactam and to evaluate its clinical response in the treatment of multidrug-resistant gram-negative bacteria (MDR-GNB) infections in China. Methods: This retrospective study evaluated the outcomes of adult patients with MDR-GNB infections treated with ceftazidime-avibactam during September 2018 to August 2020. Patients' characteristics, comorbidities, microbes, laboratory indicators and medication information were collected. The rationality of ceftazidime-avibactam clinical use, and its clinical response in the treatment of MDR-GNB infections were analyzed. Results: A total of 30 patients were included in this study, of which, 66.6% received target treatment, 26.7% received empirical treatment, and 6.7% received treatment with no indication. Only 50.0% (11/22) of patients were administrated the recommended dose according to the drug instruction or guidelines, at a median treatment duration of 10 days (range: 2-74 days). The most common source of infection was pneumonia (53.6%, 15/28). Carbapenem-resistant Klebsiella pneumoniae was the predominant pathogen (65%, 13/20). A total of 16 patients (61.5%) achieved clinical response. Patients received target treatment had higher clinical response rate than that of patients received empirical treatment (77.8% vs 25.0%, P = 0.026). A total of 11 patients (61.1%) achieved microbiological response. One patient occurred gastrointestinal adverse reactions. Conclusions: It is necessary to strengthen the monitor of the clinical application of ceftazidime-avibactam, such as the appropriate indication, reasonable dosage and duration, to improve its clinical outcome. Our results showed that ceftazidime-avibactam might be a potencial choice for the MDR-GNB infections. However, further research are still needed to identify its efficacy and safety in the real world.